Gender Discrimination in the Novel Sitti Nurbaya by Marah Rusli and the Novel Orang-Orang Blanti by Wisran Hadi: Feminist Literary Criticism - Gustia Dina; Nurizzati Nurizzati (Riviera Publishing, 2026)
This study aims to describe (1) the forms of gender discrimination against women in Marah Rusli's novel Sitti Nurbaya, (2) the forms of gender discrimination against women in Wisran Hadi's novel Orang-Orang Blanti, and (3) a comparison of gender discrimination against women in both novels. *This type of research is qualitative research using a descriptive method with content analysis techniques. This study uses a mimetic approach and an objective approach with feminist literary criticism as an analytical tool. The data sources are the novel Sitti Nurbaya by Marah Rusli and the novel Orang-Orang Blanti by Wisran Hadi. The data are speeches presented by the narrator and characters that refer to attitudes or statements containing elements of gender discrimination. Data collection techniques include reading and note-taking. Data analysis was performed in four steps: (1) describing inventoried data by tracing forms of gender discrimination, (2) classifying and coding data on phrases, clauses, and sentences regarding gender discrimination, (3) interpreting gender discrimination data to be analyzed into research findings, (4) drawing conclusions based on analyzed data.* The results indicate that, first, forms of gender discrimination in Sitti Nurbaya include marginalization (7 data), subordination (7 data), stereotypes (9 data), and violence (17 data). Second, forms of gender discrimination in Orang-Orang Blanti include marginalization (6 data), subordination (3 data), stereotypes (9 data), and violence (8 data). Third, differences in gender discrimination forms were found based on five aspects, with no double burden found in either novel.